Challenges Faced by Accredited Social Health Activists (ASHAs) in a Vulnerable Block of Odisha, India. (July 2017) - Dehury, Ranjit Kumar; Chatterjee, Suhita Chopra
Abstract: Janani Suraksha Yojna (JSY), implemented under the National Rural Health Mission (NRHM) since 2005, focused on strengthening accredited social health activists (called ASHAs) to improve maternal health in the community. The purpose of this paper is to identify various issues and challenges faced by the ASHAs in pregnancy care under JSY. Focus group discussions and in-depth interviews were conducted with ASHAs employed in tribal pockets of Jaleswar block, which may be considered a vulnerable area due to its demographic profile and inaccessible terrain. Data were analysed and grouped thematically based on government operational guidelines. The study shows ASHAs face challenges in various stages of pregnancy care, particularly during antenatal and natal stages. There are considerable limitations in identifying target groups, assisting pregnant women and in providing counseling. Many of them stem from their poor capacity to operate in vulnerable communities, thereby, showing inadequate training and capacity building of the ASHAs. The paper concludes by proposing a model for improving competency of ASHAs by taking into account both administrative as well as community inputs.